Membentuk Karakter Generasi Alpha Melalui Ajaran Panca Sradha - Purnami, I Gusti Ayu Made; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted in suranadi village which focuses on character building from an early age., The purpose of this study is to find out how the character formation of generation Alpha through the teachings of Pañca sradha. Character building is done through habituation of positive things by means of implementing each penca sradha teaching in the life or daily activities of children. The formation of children's character will be very influential, especially in crossing the transition period experienced by the alpha generation, namely in childhood to adolescence and adolescence to adulthood. Character building through the teachings of pañca sradha has a positive impact on children, as seen from the attitude and behavior of children who become better and accustomed to doing positive things in children's daily lives. The method in this study uses qualitative methods. The results of this study show that character building in alpha generation children through the teachings of pañca sradha produces good and bad children's characters. The character of children who are not good is caused because parents are not able to be good role models in the family environment. The author suggests that parents are better able to become examples or role models that can be imitated by children so that the formation of the character of alpha generation children through the teachings of pañca sradha. So that his character is formed into a successor of a quality and useful nation for the nation and state of Indonesia.